The Reinforcement of Certainty Perception on Social Media Advertisement: Dual-Process Theory Perspective - Nurul Azizah (Universitas Airlangga, 2018)
Social media offers a powerful way to promote and engage the consumer. However, there are too many information circulating on social media nowadays. This situation makes the consumers feel uncertain with the validity of information they find on social media. There are more than two million Facebook users globally, meaning that the platform still has big potential as an effective promotion tool. In this study, Social word of mouth (sWOM) theory is seen as a solution to reduce the uncertainty on the social media. Then, the dual-process theory is adapted to build the conceptual framework, which includes several variables including comment involvement, quality of comment, comment trust-ability, as well as uncertainty reduction. Item scales are adopted by the prior study and the questionnaire is composed with a back-translation technique. The collected data is tested using smart-PLS. Then the results are analyzed to observe both theoretical and managerial impact. The findings of the study suggest that all of the proposed variables have significant effect on the uncertainty reduction.